REVITALISASI PERPUSTAKAAN DESA - Machnunah Ani Zulfah (Universitas KH. A. Wahab Hasbullah Tambakberas Jombang, 2018)
This research was conducted to find out the revitalization of village libraries inJombang. This study took place in the Podoroto village library. A village with a population of7,088 people is located in the Kesamben District of Jombang Regency. The Village Library islocated in one location with the village office, located not far from educational institutionsunder the auspices of the Al Ihsani Education Foundation and the Village Market.The results of this study indicate that the implementation of the village libraryrevitalization in Podoroto village includes three things, namely restructuring, relocation andtransformation. The factors driving the revitalization of the village library are the support ofthe village and regional governments. Factors inhibiting the revitalization of the villagelibrary are the low awareness of the community, community forums, human resources,financial and facilities. Whereas the results of the village library revitalization arerestructuring which has an impact on the pace of organizations that are running well,relocation has an impact on services that are running well and transformation has the impactof developing libraries with 3 strategies, namely computer and internet services, communityInvolvement and advocacy